A framework to enhance clinical learning and teaching in undergraduate nursing education in Ghana - Kafui A. Hobenu; Anthonio O. Adefuye; Florence Naab; Champion N. Nyoni (International Journal of Africa Nursing Sciences)
Background: Nursing education is intended to produce practice-ready nurses at graduation to render high-quality care to the deserving populace. This expectation is, however, far-fetched amid the numerous challenges confronting clinical education. Although frameworks for nursing education have proved effective in guiding clinical education, nurse educators in low-income contexts acknowledge the difficulty in identifying appropriate frameworks to guide clinical education. Currently, clinical education in Ghana is compromised and fragmented, and the existing frameworks are not aligned with context-specific needs, resulting in undesirable outputs, and are not informed by practice needs or the needs of the broader community involved in clinical education. A need to develop a framework that aligns with the prevailing needs in clinical nursing education, leading to desirable outcomes, was identified. Purpose: The current study, therefore, aimed to develop a theory-informed framework to enhance clinical learning and teaching in undergraduate nursing education in Ghana. Methods: A multi-method research design underpinned by the theory of change logic model guided the development of the framework through a three-phased approach. Preceding the development of the framework, two separate studies were conducted. Triangulated data from the two earlier studies were used to develop a draft framework. Twelve (n = 12) expert stakeholders were purposively invited to participate in a one-day workshop to refine and validate the framework. Result: The final framework visualises the six theory of change logic model components, and incorporates the best available evidence and stakeholders’ inputs. Conclusion: The developed framework could enhance clinical learning and teaching in undergraduate nursing education in Ghana.